Bridging academic disciplines and policy sectors - Abelson, Julia.; Centre for Health Economics and Policy Analysis (McMaster University, 1999)
Few concepts in the social sciences literature have received as much attention from as many disciplines and policy sectors as the concept of "participation". With public participation continuing to figure prominently in debates about improved government performance and increased accountability it seems reasonable to ask: What influences participation? This paper presents a critical review of the vast, multidisciplinary literature that has examined the influences on participation with an aim to promote learning across academic disciplines and policy sectors. The review is used as a starting point for developing a framework for analyzing community-level participation in health-care decision making. A typology is presented that incorporates both qualitative and quantitative dimensions of participation. Influences on participation are organized around three predominant themes emerging from the literature: i) relationships between individual and community characteristics and participation (i.e., predisposing influences); ii) relationships between institutional actions and participation (i.e., enabling influences); and iii) relationships between interests, interest groups and participation (i.e., precipitating influences). The framework's applications are discussed in the paper and will be illustrated in an upcoming CHEPA working paper where case study results of community participation in health care decision making are presented.
Julia Abelson.
Includes bibliographical references (p. 27-31).
Also available via World Wide Web.
Keywords: Consumer Participation; Decision Making; Policy Making; Health Policy; Health Services Research; Social Responsibility